OS SERVIÇOS PRESTADOS PELOS RESTAURANTES DE PANAMBI: UMA AVALIAÇÃO DA SATISFAÇÃO E DA IMPORTÂNCIA DOS ATRIBUTOS - Siebeneichler, Tatiana; Wenningkamp, Diego; Ruchel, Ana P.; Trombini, Eduardo; Schaefer, Rogério; Zamberlan, Luciano (Salão do Conhecimento, 2013)
Resumo